2019
DOI: 10.3389/fonc.2019.01159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum CA125, CA19-9, CA72-4, and Fibrinogen-to-Lymphocyte Ratio in Gastric Cancer With Peritoneal Dissemination

Abstract: Background: Relevant serum tumor markers have been indicated to be associated with peritoneal dissemination (PD) of gastric cancer (GC). Fibrinogen has been shown to play an important role in the systemic inflammatory response (SIR) and in tumor progression. However, the clinical significance of the fibrinogen-to-lymphocyte ratio (FLR) in GC with PD has not been studied.Methods: The clinical data of 391 patients with GC were collected, including 86 cases of PD. Then, 1:3 matching was performed by propensity sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 50 publications
1
76
0
Order By: Relevance
“…Duraker and Celik ( 62 ) showed that CEA has value in the diagnosis of LNM in GC. Previous studies demonstrated that elevated levels of CA125 are associated with GC peritoneal dissemination and a poor prognosis ( 64 , 65 ). In this study, univariate analysis found that CEA, CA19-9, CA125, and CA72-4 were associated with LNM in GC, and multivariate analysis showed that CEA and CA19-9 were independent risk factors for LNM in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Duraker and Celik ( 62 ) showed that CEA has value in the diagnosis of LNM in GC. Previous studies demonstrated that elevated levels of CA125 are associated with GC peritoneal dissemination and a poor prognosis ( 64 , 65 ). In this study, univariate analysis found that CEA, CA19-9, CA125, and CA72-4 were associated with LNM in GC, and multivariate analysis showed that CEA and CA19-9 were independent risk factors for LNM in GC.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of Real World Study and Big Data for Cancer Research, the mode combining clinicopathological features and serum immunity markers to predicting the prognosis of GC is widely used in clinical. Fanotto found that the patients with higher ECOG score and lower lactate dehydrogenase (LDH) NLR had better prognosis after chemotherapy [54] Huang et al found that CA125, CA19-9, CA72-4 and Fibrinogen-to-Lymphocyte are risk factors for peritoneal dissemination among patients with GC, and used these indicators to constructe the Nomogram model [55]. We analyzed the clinical signi cance of the SIRI-PLR score through the The Gastric Cancer Information Management System v1.2 of Harbin Medical University Cancer Hospital database.…”
Section: Discussionmentioning
confidence: 99%
“…Serum tumor markers, particularly CEA, CA19-9 and CA72-4, are established biomarkers for diagnosis and disease-progress monitoring in GC patients [88]. Accumulating evidence has shown significant association between elevated CEA [89], CA19-9 [89,90,99,102], CA72-4 [88,99,102] and CA12-5 [90,[99][100][101] levels and synchronous and/or metachronous peritoneal metastasis. Specifically, CA12-5 level has shown a higher predictive performance for PD and a correlation with the degree of PD as well as the presence of malignant ascites [90,100].…”
Section: Serum Tumor Markersmentioning
confidence: 99%